2023
DOI: 10.1152/ajpendo.00187.2022
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue is not associated with cachexia or increased mortality in a retrospective study of patients with cancer

Abstract: While brown fat is strongly associated with a constellation of cardiometabolic benefits in animal models and humans, it has also been tied to cancer cachexia. In humans, cancer-associated cachexia increases mortality, raising the possibility that brown fat in this context may be associated with increased cancer death. However, the effect of brown fat on cancer-associated cachexia and survival in humans remains unclear. Here, we retrospectively identify patients with and without brown fat on fluorodeoxyglucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…These data were also confirmed in a cohort of gastrointestinal and genitourinary cancer with and without weight loss [15 ▪▪ ], indicating that mechanisms beyond thermogenesis induced by UCP1 may possibly contribute to the progression of cancer cachexia. Also, Eljalby et al [16] investigated in a large cohort of cancer patients the association between the brown fat by fluorodeoxyglucose ( 18 F-FDG) PET/CT, weight loss and mortality, observing that brown fat activation was not associated with cachexia nor with survival.…”
Section: Metabolic Changes Of Adipose Tissue During Cachexia: Brownin...mentioning
confidence: 99%
See 1 more Smart Citation
“…These data were also confirmed in a cohort of gastrointestinal and genitourinary cancer with and without weight loss [15 ▪▪ ], indicating that mechanisms beyond thermogenesis induced by UCP1 may possibly contribute to the progression of cancer cachexia. Also, Eljalby et al [16] investigated in a large cohort of cancer patients the association between the brown fat by fluorodeoxyglucose ( 18 F-FDG) PET/CT, weight loss and mortality, observing that brown fat activation was not associated with cachexia nor with survival.…”
Section: Metabolic Changes Of Adipose Tissue During Cachexia: Brownin...mentioning
confidence: 99%
“…possibly contribute to the progression of cancer cachexia. Also, Eljalby et al [16] investigated in a large cohort of cancer patients the association between the brown fat by fluorodeoxyglucose ( 18 F-FDG) PET/CT, weight loss and mortality, observing that brown fat activation was not associated with cachexia nor with survival.…”
Section: Key Pointsmentioning
confidence: 99%
“…However, the complex relationship between BAT and cancer is not yet fully understood. A retrospective study of cancer patients found that BAT was not associated with cachexia or increased mortality [ 313 ]. In contrast, another study showed that exosomal miR-155 from gastric cancer cells induced cancer-associated cachexia by suppressing adipogenesis and promoting brown adipose differentiation through C/EPBβ [ 314 ].…”
Section: Therapeutic Applicationsmentioning
confidence: 99%